How Fitness Impacts Quality of Modern Life - K.H.A.H Punsith; W.K.D. De Silva; H.D.N. Prabodhika Damayanthi; K.R.A. Perera; D.I. De Silva; H.M.P.P.K.H. Samarasekara (International Journal of Engineering and Management Research, 2022)
Health and fitness are an essential part of life. Nowadays, people come across a lot of fitness web applications that provides many diets and workout plans separately. This project is about the combination of workout and diet instruction for each member. First, a person must log in to this application by providing their name, mobile, email, height, weight, age, and gender. members can get memberships by registering, there will be a variety of memberships called as Gold, Silver, and Platinum under the price rate and time durations. Members can request an instructor. When members login into their individual user log they will be given a planned workout plan and a diet plan, which is provided by the instructor. Those workout and diet schedules for members were updated from the instructor login accordingly. For better service and ease, there is an online store for buying products related to maintaining health and diets. Users can do payments online. Members or customers can buy products from the online store by adding to the cart. This fitness training center is equipped with all the modern types of machinery and provides information about machinery data stored in the center. Services provided by the fitness training center are handled by the system administrator.